Bioinspired Nitroalkylation for Selective Protein Modification and Peptide Stapling. Issue 7 (16th January 2020) - Mahesh, Sriram; Adebomi, Victor; Muneeswaran, Zilma P.; Raj, Monika
Abstract: Nitroalkanes react specifically with aldehydes, providing rapid, stable, and chemoselective protein bioconjugation. These nitroalkylated proteins mimic key post‐translational modifications (PTMs) of proteins and can be used to understand the role of these PTMs in cellular processes. Demonstrated here is the substrate scope of this bioconjugation by attaching a variety of tags, such as NMR tags, fluorescent tags, affinity tags, and alkyne tags, to proteins. The structure and enzymatic activity of modified proteins remain conserved after labeling. Notably, the nitroalkane group leads to easy characterization of proteins by mass spectrometry because of its distinct fingerprint pattern. Importantly, the nitro‐alkylated peptides provide a new handle for site‐selective fluorination of peptides, thus installing a specific probe to study peptide–protein interactions by 19 F NMR spectroscopy. Furthermore, nitroalkane reagents can be used for the late‐stage diversification of peptides and for the synthesis of peptide staples. Abstract : Tagged : Reported is a bioinspired nitroalkylation strategy for chemoselective modification of proteins that mimics a key post‐translational modification (PTM). A variety of different tags are installed on proteins rapidly and with high conversions (99 %) under mild reaction conditions. The nitro‐peptide conjugates provide a handle for site‐selective fluorination of peptides. This strategy is applied for the stapling of peptides.